Synthesis, preparation and catalytic activities of V-doped TiO2 gel coating on porous α-Al2O3 beads - Jaroenworaluck, A.; Panyathanmaporn, T.; Soontornworajit, B.; Supothina, S.; Tawkaew, S.; Jiamsakul, Siriya; Sooknoi, T. (My University, 2007)
TiO2 and V-doped TiO2 gel were synthesized and coated onto porous α-Al2O3 beads to study the thermal catalytic activities of oxidation reactions. Titanium isopropoxide (Ti(OPr) 4) and 1,2-butadiol(Bu(OH)2) were used as starting chemicals for preparation of TiO2 gel without V-doping. After aging at ambient temperature for one week, a TiO2 gel was obtained. The concentration of Ti(OPr)4 was varied, 0.2, 0.3, 0.7 and 2.4 M was used. For V-doping of the TiO2 gel, 0.05, 0.20 and 0.75 mole% of V was prepared by ultrasonically dissolving vanadium acetylacetone (V(acac) 2) in 1,2-butadiol. The solutions were then added to Ti(OPr) 4. Finally, the mixed solutions were kept under ambient temperature for one week to form the V-doped TiO2 gel. TiO2 and V-doped TiO2 were calcined at 300, 400, 500, 600, 700, and 800°C. XRD analysis, SEM and TEM in conjunction with EDS analysis were used to identify the phases present, grain size and morphology. The TiO2 grains have a particle size in the nano-scale range. Doping TiO2 with V could retard growth of the TiO2 particles and affect phase transformation at higher calcination temperatures. Both the TiO2 and V-doped TiO2 gels were prepared and coated onto α-Al 2O3 beads to test oxidation reactions in a purpose-designed reactor. The results of the catalytic reactions indicated that V-doped TiO2 had a higher oxidation activity than the undoped TiO2 gel. The content of vanadium was related to the reaction efficiency.
Keywords: Catalytic activities